Omega-3 Long Chain Polyunsaturated Fatty Acids for Treatment of Parenteral Nutrition–Associated Liver Disease: A Review of the Literature - Tillman, Emma M (Pediatric Pharmacy Advocacy Group, 2011)
Parenteral nutrition–associated liver disease (PNALD) is a complex disease that is diagnosed by clinical presentation, biochemical markers of liver injury, concurrent use of parenteral nutrition (PN), and negative workup for other causes of liver disease. For the past 30 years, clinicians have had few effective treatments for PNALD and when disease progressed to liver cirrhosis it was historically associated with poor outcomes. Within the past 5 years there has been some encouraging evidence for the potential benefits of fish oils, rich in omega-3 long-chain polyunsaturated fatty acids (ω3PUFA), in reversing liver injury associated with PN. This article reviews the current literature relating to ω3PUFA and PNALD.